ASPEK YURIDIS TERHADAP KEBERADAAN DAN PERAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM PENGEMBANGAN MASYARAKAT - Lovelly Dwina Dahen (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACTThe increasingly rapid development of the business world has contributed to increasing the level of welfare of te Indonesian people. However, business people are not only required to benefit from their business field, but they are also required to make a positive contribution to their social environment. Changes on the level of public awareness raise new awreness about the importance of implementing Corporate Social Responsibility (CSR). This paradigm means that company is no longer an entity that only cares about itself (selfish), the exclusivity of the community, but a legal entity (recht persoon) that is obliged to adapt culturally to its social environment, and can be held accountable like legal subjects at generally. Based on this paradigm, CSR, which was previously carried out in the sense of being voluntary, is now mandatory. Theoretically, CSR is the core of business ethics, where a company not only has economic and legal obligations to shareholders, but the company also has obligations to othe interested partied (stakeholders). The concept of CSR that has been normalized in laws and regulations must be inmplemented properly to realize the goals of the norm. So that the shift in the concept of CSR which was originally voluntary to mandatory can play a role in community development. The CSR must be carried out in a sustainable manner, so that the community can also grow simultaneously with the growth and development of the company